«WHO STANDS TO THE END THOSE WILL SURVIVE!»: ATTEMPT OF HISTORY REGENERATION OF EVERYDAY LIFE OF UNDERGROUND GREEK-CATHOLIC PRIEST YAROSLAV SIRETSKY - Єгрешій, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the scientific article the author paid attention to the didactic-christian reasons of Greek-Catholic priest Yaroslav Siretsky’s private correspondence.